An investigation into the National Water Act No 36 of 1998: Its impact and effectiveness on stakeholders in a Water Users' Association in a rural community in the Western Cape - Andre Marshall Thops (Graduate School of Business (GSB), 2024)
This study investigates the possible failure and the reasons for the failure of the policies and strategies of the National Water Act (NWA) of 1998 and the impact on the rural community of the Hex River Valley. This study interrogates the negligence to implement the policies and strategies of the NWA to redress the practice of segregated use of the water resource as a natural resource and the failure to address the pro-poor visions of the NWA. This investigation furthermore looks at the role and impact of policies and strategies of the NWA on responsibilities of the Water Users' Association (WUA) of the Hex River Valley as the bulk water management structure of the community and the Breede-Gouritz Catchment Management Agency (CMA) in its role as management agent representing the Department of Water and Sanitation (DWS) at grassroots level. This study, through a research strategy, reached the conclusion that the ANC government has failed to implement the strategies and policies of the National Water Act no.36 of 1998 to implement equitable water sharing. A deductive approach, using qualitative data, was used to address the research question. This research method was used to uncover trends and patterns in thoughts and opinions of rural communities regarding the NWA, its policies and strategies